Between belief and fear - Reinterpreting prone burials during the Middle Ages and early modern period in German-speaking Europe - Alterauge, Amelie; Meier, Thomas; Jungklaus, Bettina; Milella, Marco; Lösch, Sandra (PLOS ONE, 2020)
Prone burials are among the most distinctive deviant burials during the Middle Ages and early modern period. Despite their worldwide distribution, the meaning of this burial practice is still a matter of debate. So far, a comprehensive analysis of prone burials is lacking for Central Europe. By compiling evidence from Germany, Switzerland and Austria, this study investigates how these findings fit into the scope of medieval funerary practices. 95 prone burials from 60 archaeological sites were analyzed regarding geographical distribution, dating, burial features, body position, age-at-death and sex. We applied descriptive statistics accompanied by multiple correspondence analysis in order to highlight possible multivariate patterns in the dataset. Prone burials occur in funerary and non-funerary contexts, with a predominance of single churchyard burials, followed by favored and exterior location and settlements. In terms of grave features, the majority of churchyard burials do not differ from regular graves. Multivariate patterns appear to reflect diachronic changes in normative burial practices. We found a significant correlation between burial location and dating, due to a higher frequency of high medieval males in favored locations. In these cases, prone position is interpreted as a sign of humility, while similar evidences from late and post-medieval times are seen as an expression of deviancy. Apparent lack of care during burial reveals disrespect and possible social exclusion, with inhumations outside consecrated ground being the ultimate punishment. In some regions, apotropaic practices suggest that corpses should be prevented from returning, as attested in contemporaneous sources and folk beliefs. We hypothesize that the increase of prone burials towards the late and post-medieval period is linked to such practices triggered by epidemic diseases. The multiplicity of meanings that prone position might have in different contexts demands for careful interpretations within the same regional and chronological frame.